Kontribusi Sertifikasi Guru, Motivasi Kerja, dan Supervisi Akademik Terhadap Kinerja Guru Sekolah Dasar di Gugus III Kecamatan Penebel Kabupaten Tabanan - Yulastiningtiyas, Ni Wayan; Sulindawati, Ni Luh Gede Erni; Werang, Basilius Redan (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to (1) describe the contribution of teacher certification to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency, (2) describe the contribution of work motivation to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency, (3) describe the contribution of academic supervision to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency, (4) describe the contribution of teacher certification, work motivation, and academic supervision together to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency. This study is an "ex-post facto" study with a sample size of 35 taken using the proportional random sampling technique from a population of 38 schools. Data were collected using a questionnaire. Data analysis was carried out using the product moment correlation technique, multiple regression, and partial correlation. The results of the study show that: (1) there is a positive and significant contribution of teacher certification to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency with a correlation coefficient of 0.520 and an effective contribution of 12.28%, (2) there is a positive and significant contribution of work motivation to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency with a correlation coefficient of 0.653 and an effective contribution of 24.49%, (3) there is a positive and significant contribution of academic supervision to the performance of elementary school teachers in Cluster III, Penebel District, Tabanan Regency with a correlation coefficient of 0.679 and an effective contribution of 26.63%, (4) there is a positive and significant contribution together of teacher certification, work motivation and academic supervision to the performance of elementary schools in Cluster III, Penebel District, Tabanan Regency with a correlation coefficient of 0.796 and a contribution of 63.4%.